Diseño de un modelo de dirección, planeación y control de gestión para los establecimientos comerciales dedicados a la venta de abarrotes y lichigo. caso: autoservicio Merk Offer (2017)
The purpose of this document is to help and understand in detail the management carried out in the main activities of the Autoservicio Merk Offer, through a management, planning and control model that comprehensively adopts all the procedures that must be performed to manage the entity. . To achieve the above, in the first instance requires the recognition of the commercial entity, the types of surfaces, distribution models and forms of customer service, emphasizing neighborhood stores, mini markets and supermarkets